Perspektif Gen Z Politeknik Pariwisata Bali terhadap Peranan Sosial Media dalam Mengembangkan Bisnis Kuliner - Santi Diwyarthi, Ni Desak Made; Adi Pratama, Wayan; Jata, I Wayan; Mas Wiartha, Nyoman Gede (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
This research explored the perspectives of Generation Z at Politeknik Pariwisata Bali on the role of social media in shaping entrepreneurship in culinary business. The study employs a quantitative approach, utilizing questionnaires, observations, and interviews to collect data from a sample of 100 Generation Z students majoring in Hotel Management Study Program. The results of the analysis indicate that the majority of respondents (95%) view social media as a source of inspiration and a platform for interaction for young entrepreneurs. Additionally, 87% expressed that the institution has provided adequate avenues for entrepreneurship in culinary business through internet networking (87%), entrepreneurship-related events or activities (92%), and the Student Activity Unit at Politeknik Pariwisata Bali (78%). However, there were findings regarding potential negative impacts of social media on entrepreneurial character, such as perceptions of instant success (86%) and a perceived lack of management involvement in organized activities (86%). These findings underscore the importance of adopting a thoughtful approach in integrating social media to support the development of entrepreneurship in culinary business among Generation Z, particularly those at Politeknik Pariwisata Bali.